The association between ultra-processed food consumption and adiposity indexes in adults living in Tehran: a dose-response analysis within a cross-sectional study - Mahsa Ranjbar; Neda Asgari Avini; Sakineh Shab-Bidar (BMC Public Health)
Abstract Background Ultra-process foods (UPF) were suspected to induce many diseases and threaten consumers’ health. The aim of this study was to examine the association between the consumption of highly processed foods and adiposity indexes in Tehranian adults. Method In a cross-sectional design, 850 Tehranian adults were included. NOVA classification was used to assess the intake of UPF in participants. The amount of calorie intake through processed foods was assessed. Adiposity indexes outcomes include body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), visceral adiposity index (VAI), body roundness index (BRI), and body adiposity index (BAI). Lipid accumulation product (LAP) and triglyceride-glucose index (TyG) were also assessed. Binary logistic regression was used to evaluate the association between the intake of UPF and adiposity indexes measurements. Result there was a higher intake of UPF in men than women (p < 0.001). The results of logistic regression revealed that there is a significant association between intake of UPF with WHR (odds ratio (OR): 1.09, 95% confidence interval (CI): 0.73–1.61) and BRI (OR: 2.10, 95% CI: 1.38–3.19) in the crude model. Nevertheless, after adjusting for confounders, the results were insignificant (WHR: OR, 0.77, 95% CI, 0.46–1.27, and BRI: OR, 1.70, 95% CI, 1.05–2.73). No significant association was seen for other outcomes (p > 0.001 for all). The results of dose-response analyses revealed a substantial association between UPF intake and BMI, WHrT, WC, VAI, BRI, BAI, LAP, and TyG. Conclusion UPF consumption was significantly related to increased risk of high-risk adiposity indexes in the dose-response analysis. More studies are needed to strengthen the results of this study.